SURG-42. MOLECULAR PROFILE CONSENSUS CLUSTERING DEFINES CLINICALLY DISTINCT GROUPS IN IDH WILD-TYPE GLIOBLASTOMA. (14th November 2022) - Gersey, Zachary; Mallela, Arka; Zhang, Xiaoran; Pease, Matthew; Abdelhakiem, Mohamed; Pearce, Thomas; Lieberman, Frank; Mantica, Megan; Phillips, Richard; Bagley, Stephen; Nasrallah, MacLean; Binder, Zev; et al.
Abstract: OBJECTIVES: Although the impact of surgery in glioblastoma (GBM) is well-established, there is insufficient data to determine how surgical resection affects overall survival (OS). The impact of other GBM genomic alterations on EOR-induced survival remains poorly understood. Here, we leverage a large cohort of GBM patients with genomic data to establish the impact of genomic alterations on resection-dependent overall survival in GBM. METHODS: 537 IDH WT GBMs from UPMC were analyzed using Glioseq next generation sequencing panel. Using molecular profiles derived from Glioseq data, semi-supervised Monte Carlo reference-based consensus clustering was used to define 5 distinct groups. Cox Proportional Hazards models were used to identify predictors of OS within molecular groups. RESULTS: Clustering of 537 IDH wild-type GBM identified 5 distinct groups: 1: TERT mutated/MGMT methylated/EGFR mutated or gain; 2: TERT mutated /MGMT methylated/p53 mutated; 3: TERT WT; 4: TERT mutated/MGMT methylated/CDKN2A loss; 5: TERT mutated/MGMT unmethylated. Thresholds in postoperative residual contrast enhancing volume (rCEV) and residual non-contrast enhancing volume (rNCEV) were identified which marked significant differences in median overall survival (MOS) between molecular groups in rCEV -Group 1: 11.7cc, Group 2: 14.4cc, Group 3: 1.1cc, Group 4: 0.1cc, and Group 5 1.1cc. Sex, age, KPS >70, temozolomide, and radiation along with thresholded rCEV and rNCEV were used in multivariate Cox analyses. Groups demonstrated distinct predictors of OS: radiation only in Group 1 tumors, low rCEV in Group 2 tumors, younger age, temodar, low CEV, and KPS >70 in Group 3 tumors, female sex, younger age, radiation, KPS >70 low rCEV in Group 4 tumors, and KPS >70, temodar, and low rCEV in Group 5 tumors. CONCLUSIONS: Clustering results suggest that there are clinically distinct molecular groups of IDH wild-type glioblastomas. Age, sex, KPS >70, temozolomide treatment, radiation therapy, and EOR have varying affects on these molecular groups.